HUBUNGAN ANTARA KARAKTERISTIK IBU DAN KELUARGA DENGAN PRAKTIK KELUARGA SEHAT DI WILAYAH KERJA PUSKESMAS LASEM KABUPATEN REMBANG - Fita Rizqi Riyansari; Ayun Ariatmi; Antono Suryoputro (Jurnal Kesehatan Masyarakat (Undip), 2017)
Keluarga Sehat approach is a new program of Health Ministry that will be used to measure family health in 2017. Family health in work area of Puskesmas Lasem based on PHBS approach in 2015 is 34,1%, fewer than national target 80%. The aim of this research is to analyze the correlation between characteristic of housewife and family with practice of keluarga sehat in work area of Puskesmas Lasem. This analytic-survey research uses cross sectional study and combains quantitative method used quetionnair guide and qualitative method used in-depth interview. Population is 2.793 families that has toddler and sampel is 120 choosen propotional randomly. Bivariat analysis is counted by chi square test with 95% of significancy between characteristic of housewife and family with practice of keluarga sehat. The result showed that respondents are in healthy reproduction age (20-35  years old)(76,7%), elementary educated (75,8%), not employer (79,2%), having family member ≤4 (79,2%), and having revenue ≥ UMR (75,8%). Bivariat test showed that there is no correlation between housewife age, housewife education level, housewife occupation status, and total of family member with practice of keluarga sehat. There is correlation between family revenue with practice of keluarga sehat. It is recomended that Puskesmas Lasem analyze the need of resource that support Keluarga Sehat program and manage sosialization by associating with family characteristic.